Persuasion theory & research - O'Keefe, Daniel J. (Current communication: an advanced text series, 2002)
This comprehensive text provides a thorough and critical treatment of persuasion theory and research from a social science perspective. Daniel J. O'Keefe includes a discussion of research on the production of persuasive messages as well as more traditional research on the study of message effects. The new edition contains more coverage of the theory of reasoned action, a new chapter on functional approaches to attitude, a new chapter on behavioral change, new material on persuasive campaigns, and updated research citations and examples.